The phenomenon of intrinsic value of nature - Loginovskaya, Ludmila M. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
A study of the intrinsic value of nature was conducted. The relationship between the types of value (extrinsic and intrinsic) and approaches to its understanding (subjective and objective) was established. For the first time, a holistic concept was developed which defined the essence and characteristics of the intrinsic value of nature, identified the criteria for its detection, and formulated the definition of the concept of «intrinsic value of nature». The theoretical and methodological foundations of the intrinsic value of nature for living beings, inanimate components and ecosystems are presented. The need to establish harmonious and respectful relationships between humans and their moral partner, the natural world, is ethically substantiated. Recommendations are given for the practical application of the results of this study.
Keywords: intrinsic value of nature; extrinsic value of nature; instrumental value; terminal value; moral status of nature; inherent worth; environmental ethics